2016
DOI: 10.1083/jcb.201604115
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 nuclear dynamics and target recognition in living cells

Abstract: How CRISPR Cas9–guide RNA complexes navigate the nucleus and interrogate the genome is not well understood. Ma et al. track these complexes in live cells and find that mutations in the guide seed region significantly reduced the complex’s target residence time, with a commensurate impairment of cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
175
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 38 publications
16
175
0
3
Order By: Relevance
“…The Shield1- and doxycycline-inducible dSpyCas9-mCherry-APEX2 construct was made by subcloning Flag-APEX2 from Flag-APEX2-NES (Addgene 49386) into DD-dSpyCas9-mCherry 21 using the pHAGE backbone. Two additional NLSs (SV40 and nucleoplasmin NLS) were inserted at each terminus to improve nuclear localization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Shield1- and doxycycline-inducible dSpyCas9-mCherry-APEX2 construct was made by subcloning Flag-APEX2 from Flag-APEX2-NES (Addgene 49386) into DD-dSpyCas9-mCherry 21 using the pHAGE backbone. Two additional NLSs (SV40 and nucleoplasmin NLS) were inserted at each terminus to improve nuclear localization.…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviral transduction was as described 21 . Six-fold higher titers of sgRNA-encoding lentiviruses were used for transduction relative to dSpyCas9-APEX2 lentivirus.…”
Section: Methodsmentioning
confidence: 99%
“…143 More recently, they have been adapted to allow high-resolution super-resolution imaging of up to 30 genomic loci using short oligonucleotide probes 144 or up to 6 loci using modified CRISPR-based systems targeted to the genome by engineered guide RNAs. 145,146 Although both approaches have their drawbacks, they represent significant improvements over traditional FISH analysis yet can still detect only a tiny fraction of the genomewide contacts seen with Hi-C. 144,[147][148][149][150] However, improvements and innovative new approaches are certainly on the horizon. Optical imaging can also capture chromosome dynamics and 3D positioning of loci in live cells, neither of which can be determined using static…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Single-molecule experiments have demonstrated that Cas9 initiates the target DNA search process by probing for a proper PAM sequence before interrogating the flanking DNA for potential guide RNA complementarity (94). Target recognition occurs through three-dimensional collisions, in which Cas9 rapidly dissociates from DNA that does not contain the appropriate PAM sequence, and dwell time depends on the complementarity between guide RNA and adjacent DNA when a proper PAM is present (55,61,94). Once Cas9 has found a target site with the appropriate PAM, it triggers local DNA melting at the PAM-adjacent nucleation site, followed by RNA strand invasion to form an RNA-DNA hybrid and a displaced DNA strand (termed R-loop) from PAM-proximal to PAM-distal ends (94,96).…”
Section: Target Search and Recognitionmentioning
confidence: 99%